Meningkatkan kualitas proses belajar mengajar melalui fungsi pengawasan dalam manajemen mutu terpadu di Wilayah Kepengawasan Gugus Sekolah 05 Kecamatan Magersari Kota Mojokerto - Sunarijah (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Building the quality of education continues to be done, both by the government and the school as education providers. In an effort to meet the needs and demands of society on the quality of education and simultaneously as a response to the changes of life very quickly in the era of globalization. For that reason researchers need research on improving the quality of teaching and learning process through supervisory function in the integrated quality management in the District Kepengawasan Cluster 05 District Magersari Mojokerto City. This research uses action research for three cycles. Each cycle consists of one meeting each of which consists of four stages: design, activity and observation of reflection and revision. The target of this research is Master of Kepengawasan District School Cluster 05 Magersari Subdistrict Mojokerto City 15 people. The data obtained in the form of the results of supervision assessment of teaching and learning process. The success of the learning process in cycle III shows that the cycle can be stopped because it has met the target of> 70%. This is evident from the average increase in teacher performance per cycle. The conclusions of this research are: The quality of teaching and learning process through supervisory function in integrated quality management in Kepengawasan Area School Cluster 05 Magersari Sub-district Mojokerto City has increased, it can be seen from the average of teacher performance improvement from 65,87 percent in cycle I, to 76.67 in Cycle II and increased to 82.86 percent in Cycle III.